Inovasi Pembuatan Handsanitizer dan Pencegahan Penyakit Menular Melalui Pemberdayaan Wanita - Dharmayanti, Agustin Wulan Suci; Tsalis, Dina; Indriana, Tecky; Fatmawati, Dwi Warna Aju; Permatasari, Yulita Indah (Fakultas Kedokteran Gigi, Universitas Jember, 2025)
In recent years, the Covid-19 pandemic has highlighted the importance of personal hygiene to prevent the spread of infectious diseases. This article examines the innovation of natural ingredient-based hand sanitizer production and the empowerment of women through training in Dusun Krajan, Lengkong Village, Mumbulsari District, Jember. By providing education and practical training in making hand sanitizer and moringa leaf tea, this initiative aims to enhance women's capacity to maintain family and community health. The training results indicate an increase in participants' knowledge and skills in producing safe sanitation and strengthening women's participation in public health. In conclusion, the empowerment of women through this initiative can enhance the well-being of families and communities as a whole.Keywords: battle leaves, hand sanitizer, infectious diseases, moringa tea, women empowerment